An Analysis of Illocutionary Acts in Azzam’s Character in Novel Ketika Cinta Bertasbih - Rina Mulya; Kismullah Kismullah; Lismalinda Lismalinda (Universitas Syiah Kuala, 2020)
This research is analyzing of illocutionary acts performed by the main character Azzam in the novel Ketika Cinta Bertasbih. It is an Islamic novel. This research applied Searle’s theory and his 5 classifications, which are assertives, directives, commissives, expressives, and declaratives. This research used a qualitative method. Based on the findings of this research all of the types of illocutionary acts were found in this novel. The most common type found in this novel is directives. The reason is that Azzam, the main character, is described as someone who is hardworking, honest, and firm. These characteristics earn him respect from people around him and this gives him more opportunity to speak in a directive way. Therefore, ini this novel Azzam used a lot of directive type. The findings also showed that the types of illocutionary acts used by the main character in this novel are different from those used by the main character in fiction novels in earlies studies.